Short-Term Association between Sulfur Dioxide and Mortality: A Multicountry Analysis in 399 Cities - O’Brien, Edward (2023)
Background: Epidemiological evidence on the health risks of sulfur dioxide (sulfur dioxide SO2) is more limited compared with other pollutants, and doubts remain on several aspects, such as the form of the exposure–response relationship, the potential role of copollutants, as well as the actual risk at low concentrations and possible temporal variation in risks. Objectives: Our aim was to assess the short-term association between exposure to sulfur dioxide SO2 and daily mortality in a large multilocation data set, using advanced study designs and statistical techniques. Methods: The analysis included 43,729,018 deaths that occurred in 399 cities within 23 countries between 1980 and 2018. A two-stage design was applied to assess the association between the daily concentration of sulfur dioxide SO2 and mortality counts, including first-stage time-series regressions and second-stage multilevel random-effect meta-analyses. Secondary analyses assessed the exposure–response shape and the lag structure using spline terms and distributed lag models, respectively, and temporal variations in risk using a longitudinal meta-regression. Bi-pollutant models were applied to examine confounding effects of particulate matter with an aerodynamic diameter of less than or equal to 10 micrometers≤10μm (particulate matter begin subscript 10 end subscriptPM10) and 2.5 micrometers2.5μm (particulate matter begin subscript 2.5 end subscriptPM2.5), ozone, nitrogen dioxide, and carbon monoxide. Associations were reported as relative risks (RRs) and fractions of excess deaths. Results: The average daily concentration of sulfur dioxideSO2 across the 399 cities was 11.7 micrograms per meter cubed11.7 μg/m3, with 4.7% of days above the World Health Organization (WHO) guideline limit (40 micrograms per meter cubed40 μg/m3, 24-h average), although the exceedances occurred predominantly in specific locations. Exposure levels decreased considerably during the study period, from an average concentration of 19.0 micrograms per meter cubed19.0 μg/m3 in 1980–1989 to 6.3 micrograms per meter cubed6.3 μg/m3 in 2010–2018. For all locations combined, a 10 microgram per meter cubed10-μg/m3 increase in daily sulfur dioxide SO2 was associated with an RR of mortality of 1.0045 [95% confidence interval (CI): 1.0019, 1.0070], with the risk being stable over time but with substantial between-country heterogeneity. Short-term exposure to sulfur dioxide SO2 was associated with an excess mortality fraction of 0.50% [95% empirical CI (eCI): 0.42%, 0.57%] in the 399 cities, although decreasing from 0.74% (0.61%, 0.85%) in 1980–1989 to 0.37% (0.27%, 0.47%) in 2010–2018. There was some evidence of nonlinearity, with a steep exposure–response relationship at low concentrations and the risk attenuating at higher levels. The relevant lag window was 0–3 d. Significant positive associations remained after controlling for other pollutants. Discussion: The analysis revealed independent mortality risks associated with short-term exposure to sulfur dioxideSO2, with no evidence of a threshold. Levels below the current WHO guidelines for 24-h averages were still associated with substantial excess mortality, indicating the potential benefits of stricter air quality standards.